The Status and Influencing Factors of Cyberchondria During the COVID-19 Epidemic. A Cross-Sectional Study in Nanyang City of China - Peng, Xiao-Qing; Chen, Yang; Zhang, Yi-Chuan; Liu, Fei; He, Hai-Yan; Luo, Ting; Dai, Ping-Ping; Xie, Wen-Zhao; Luo, Ai-Jing (Frontiers in Psychology, 2021)
Cyberchondria is considered “the anxiety-amplifying effects of online health-related searches.” During the COVID-19 pandemic, people are likely to search health-related information online for reassurance because of fear and related physical symptoms, while cyberchondria may be triggered due to the escalation of health anxiety, different online seeking behavior preference, information overload, and insufficient e-health literacy. This study aimed to investigate the status and influencing factors of cyberchondria in residents in China during the epidemic period of COVID-19. The participants were 674 community residents of Nanyang city surveyed from February 1 to 15, 2020. We administered online measures, including the Chinese Short Form of the Cyberchondria Severity Scale (C-CSS-12), Short Health Anxiety Inventory (SHAI), eHealth Literacy Scale (eHEALS), Patient Health Questionnaire-15 (PHQ-15), and COVID-19-related online information seeking behavior questionnaire. In our study, the average C-CSS-12 total score of residents was 30.65 ± 11.53 during the virus epidemic; 25% of participants scored 22 or below, 50% scored 23 to 38, and 21.9% scored 39 to 60. The SHAI total score (β = 0.598 > 0, P < 0.001), the use of general search engines (β = 1.867 > 0, P = 0.039), and searching for information on how to diagnose COVID-19 (β = 2.280 > 0, P = 0.020) were independent risk factors for cyberchondria, while searching lasting less than 10 min each (β = −2.992 < 0, P = 0.048), the use of traditional media digital platforms (β = −1.650 < 0, P = 0.024) and professional medical communication platforms (β = −4.189 < 0, P = 0.007) were independent protective factors. Our findings showed that nearly a quarter of the participants scored 39 or higher on the C-CSS-12 in Nanyang city during the pandemic, which should be taken seriously. Health anxiety and COVID-19-related online information seeking behavior including online duration, topics and choice on different information channels were important influencing factors of cyberchondria. These findings have implications for further research and clinical practice on cyberchondria in China.